DAMPAK AKUNTANSI FORENSIK DAN AUDIT INVESTIGASI DALAM MENDETEKSI FRAUD PENGADAAN BARANG/JASA - Retno Ratu Wiharti; Novita novita (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2020)
The purpose of this study was to determine the effect of the forensic accounting and audit investigations in detecting fraud procurement of goods and services. The rise of fraud cases in Indonesia, one of which is fraud related to public needs, namely the procurement of goods and services. This is reminiscent of the real threat of fraud in the form of corruption in the procurement of goods and services that can cause poor quality of goods / services produced so that they cannot serve the public interest effectively and efficiently. In this context, the community is the most disadvantaged party. Collecting data in this study through the distribution of questionnaires with a total sample of 34 auditor respondents in the field of Investigation of the Badan Pemeriksa Keuangan dan Pembangunan DKI Jakarta. This research uses PLS (Partial Least Square) analysis technique, using SmartPLS software testing tool version 3.2.8. The results of this study indicate that the results of the analysis of the application of forensic accounting and investigative audits have a significant effect in detecting fraud procurement of goods / services.